Sojourner Truth papers - Truth, Sojourner, -1883.
Four ALsS (no year May 12, 1853 April 15, 1855 July 23, and 1864 February 25) written by Truth to Mary K. Gale; ALS (1871 September 27) to Gale from D. H. Morgan; two ALsS (1873 September 14 and 1876 March 31) to Gale from Frances W. Titus; and biographical material, newspaper clippings, printed matter, and photographs of or relating to Truth.
African American abolitionist and reformer. Born circa 1797. Legal name: Isabella Van Wagener.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gale, Mary K. -- Correspondence; Morgan, D. H., -- active 1871 -- Correspondence; Titus, Frances W. -- Correspondence; African American abolitionists; Antislavery movements; Social reformers; Abolitionists; Reformers